How Transformational Leadership and Work Discipline Shape Police Personnel Performance - Istiawan, Indah Ramadhani; Earlyanti, Novi Indah; Prisgunanto, Ilham; Halimah, Halimah (International Journal of Economics Development Research (IJEDR), 2025)
The objective of this research is to assess the influence of financial literacy on the performance The performance of police personnel at the Magetan Resort Police (Polres) experienced a decline in 2023 compared to 2022 across three key criteria. To address this issue, it is essential that personnel demonstrate improved performance. This study aims to examine the partial and simultaneous effects of transformational leadership and work discipline on the performance of police personnel at the Magetan Resort Police. Utilizing a quantitative approach with a survey method, the research targeted a population of 378 personnel, from which a sample of 160 was selected using the Slovin formula and simple random sampling. Data were collected through questionnaires consisting of 8 items each for transformational leadership, work discipline, and performance variables, measured using a Likert scale. Data analysis involved instrument validity and reliability tests, classical assumption tests, and hypothesis testing. The findings reveal that both transformational leadership and work discipline have a positive and significant effect on personnel performance, both individually and jointly. The regression model obtained is ? = 0.883 + 0.055X? + 0.970X?, with an F-calculated value of 8138.029. The Adjusted R Square value of 0.990 indicates that transformational leadership and work discipline account for 99% of the variation in personnel performance, with only 1% influenced by other factors. These results highlight the critical role of effective leadership and disciplined work behavior in enhancing police performance.